Sosialisasi CPPB-IRT untuk Meningkatkan Kesadaran Keamanan Pangan Produk Lokal Masyarakat Desa Bintang Rinjani - Firman Fajar Perdhana; Made Gendis Putri Pertiwi; Baiq Haulia Ariyanti; Rendi Gunawan; Fitri Inayati; Alfu Laily; Rizki Muhammad Ibnu Sabilillah; Mulia Aridho; Rizal Fahmi; Nila Susila Wati; Mey Rizka R. Putri; Risna Lestari (Rengganis Jurnal Pengabdian Masyarakat, 2026)
Bintang Rinjani Village possesses abundant agricultural potential, yet food downstreaming is hindered by low literacy in food safety and business legality. This community service activity aims to socialize Good Manufacturing Practices for Home Industries and the licensing procedures for Food Production Certificate for Home Industry. The program was conducted in January 2024, involving 24 participants through interactive lectures and discussions using visual media. The effectiveness was measured using pre-test and post-test instruments with a 4-point Likert scale. Analysis results showed a significant increase in participants' understanding, with the average score rising by 21.35%, from 58.13% (moderate criteria) to 79.48% (high criteria). In conclusion, this program successfully enhanced community literacy toward food safety standards and legal aspects, serving as a crucial foundation for developing competitive and consumer-safe local home industries.